Desirable PVDF hollow fiber membrane engineered with synergism between small molecular weight additives for DCMD treating of a hypersaline brine. (February 2022) - Zou, Lusi; Zhang, Guoyin; Yu, Jianjia
Abstract: Developing membrane for brine waste reclamation via direct contact membrane distillation (DCMD) requires specially membrane characteristics engineering. Toward practical and scalable hydrophobic micromembrane with desirable properties, attaining energy-efficient and durability during hypersaline treatment remains a great challenge. Herein, polyvinylidene fluoride (PVDF) hollow fiber (HF) membranes were developed for particular use in DCMD for treating hypersaline (100, 000 mg/L of NaCl solution) via adopting mixture of small molecular weight (MW) additives, including water, lithium chloride (LiCl), and ethylene glycol (EG). Engineered to suppress the limitation of single small MW additives only possessing a unique enhancement in the tailoring of specific properties for improving the partial DCMD performance, the research emphasis is placed on the synergistic effect between small molecular weight additives, resulting in a much-enhanced performance. The dope solution of PVDF/LiCl/H2O/N-Methyl-2-pyrrolidone (NMP) = 12/2/2/84 (wt%) spun HF membrane, P-L-W2, has been shown to reveal the most desirable membrane characteristics for DCMD, including comparable porosity (ε, 74.2 ± 0.4%), superior liquid entry pressure (LEP, 3.05 bar), and robust mechanical properties. The P-L-W2 membrane also exhibited enhanced water flux, energy efficiency, and anti-wetting ability in comparison with the neat PVDF HF membrane. With advantage of easy implement, the concept of adoption of additives mixture provides a novel platform to customize desirable PVDF HF membranes with enhanced DCMD performance.